2003
DOI: 10.2519/jospt.2003.33.11.639
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Altered Lower-Extremity Kinematics on Patellofemoral Joint Dysfunction: A Theoretical Perspective

Abstract: Although patellofemoral pain (PFP) is recognized as being one of the most common disorders of the lower extremity, treatment guidelines and underlying rationales remain vague and controversial. The premise behind most treatment approaches is that PFP is the result of abnormal patellar tracking and/or patellar malalignment. Given as such, interventions typically focus on the joint itself and have traditionally included strengthening the vastus medialis oblique, taping, bracing, soft tissue mobilization, and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
600
9
55

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 793 publications
(680 citation statements)
references
References 41 publications
16
600
9
55
Order By: Relevance
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…17,21,24,25 Theoretically, weakness of the hip abductors and external rotators may be associated with poor control of eccentric femoral adduction and internal rotation during weight-bearing activities, leading to misalignment of the patellofemoral joint as the femur medially rotates underneath the patella. 21,22 Consequently, to reduce excessive lateral patellar deviations during weight-bearing activities and potentially reduce anterior knee pain, physical therapy intervention may need to address hip muscle performance to facilitate greater control of weightbearing femoral adduction and internal rotation. Specific activities targeting performance of the lateral hip musculature have been incorporated into physical therapy intervention programs for improving pain, disability, and function in patients with PFPS.…”
Section: 726mentioning
confidence: 99%
“…This increased Q angle leads to patella subluxation, which intensifies the patellofemoral peak pressure, one of the causes of PFPS (31,32,33). In addition, weakness in these muscles may cause patellar facet overload (13,34).…”
Section: Discussionmentioning
confidence: 99%